O Pagamentos por serviços ambientais no Brasil e a função social dos imóveis rurais - Silva, Keilla Ingrid (2020)
Law n. 12,651 / 2012, established in the Brazilian legal system a new perception of ecological preservation, the establishment of Payments for Environmental Services (PSA) involves financial mechanisms for the protection of nature. In this context, considering that the social function imposed on rural properties provides for levels of agricultural productivity, some PSAs authorize properties to remain without production, only providing services that preserve nature. Given this, it is apprehended that the PES could release the fulfillment of the social function, and, therefore, prevent the implementation of agrarian reform. This work seeks to analyze whether this statement is necessary, if the PSA can, in fact, make the social function and agrarian reform unfeasible, due to dispensing with the agricultural productivity of rural properties. To this end, we seek to understand how the social function institute has been applied in the country, and how agrarian reform is being carried out, realizing, still, what the PES are and the proposal in which it is inserted, the green economy. The analysis will be based on the perceptions of Jose Gomes da Silva on land reform, Amyra El Khalili on the financialization of nature, and Ricardo Abramovay's conception of growth and green economy.